Inequalities in initiation of COVID19 vaccination by age and population group in Israel- December 2020-July 2021 - Yanay Gorelik (Elsevier, 2022)
Summary: Background: COVID19 vaccination coverage in Israel varies among population groups. Comparing crude coverage between groups is misleading because of different age structures and socio-economic differences. To describe inequalities in COVID19 vaccine initiation in Israel we analysed the interaction of age and population groups in terms of dose 1 vaccine coverage Methods: We calculated cumulative age-specific first COVID19 vaccine coverage by population group (Ultra-Orthodox Jewish, Arab, General Jewish). We calculated the relative differences in vaccine coverage between population groups within each age group, and between age groups within each population, using ANOVA and binomial regression after adjusting for socio-economic status Findings: 8,507,723 individuals in 268 cities were included. Compared with the general Jewish population, coverage was lowest in the Ultra-Orthodox population in all age groups (range -12% among 60+ to -52.8% among 10-19 years olds, p<0.001). In all groups, the proportion of vaccinated individuals in younger age groups relative to those aged 60+ decreased with decreasing age and were smallest in the Ultra-Orthodox groups. For example, within the general Jewish population, people aged 20-29 were 14% less likely to be vaccinated than those aged 60+ while within the Ultra-Orthodox population it was 34.5% Interpretation: In all age groups, the Ultra-Orthodox population had the lowest vaccine coverage. Differences persisted after adjusting for socio-economic status. The younger the age group, the more Ultra-Orthodox Jews were diverging from age peers in terms of initiating COVID19 vaccination, suggesting a generational effect. Tailored approaches are urgently required to encourage vaccination among under-immunized groups in Israel Funding: No specific funding was received